On the credibility of the Irish pound in the EMS - Ledesma-Rodriguez, Francisco; Navarro-Ibanez, Manuel; Perez-Rodriguez, Jorge; Sosvilla-Rivero, Simon (Economic & Social Studies, 2000)
This paper assesses the degree of credibility of the Irish Pound in the European Monetary System between 1983 and 1997. Different credibility indicators proposed in the literature are used to measure agents? perceptions of the credibility of the ERM commitment in an attempt to distinguish between events stemming from problems in the ERM itself and those that appear to have been exclusive to Ireland.
Keywords: Irish pound; European Monetary System; Ireland